The global burden of chronic and hidden hunger revisited: New panel data evidence spanning 1990–2017 - Lenaerts, Bert; Demont, Matty (Elsevier, 2021)
Gödecke, Stein and Qaim (2018) (GSQ) recently analysed the 1990–2010 trend and determinants of the global burden of chronic and hidden hunger. We reanalyse and extend GSQ's study and demonstrate that after 2010, significant reductions in the burden of hunger were achieved. In contrast with GSQ, we find that (i) hidden hunger is more prevalent than chronic hunger; (ii) cereal availability and the supply of vegetables and fruits matter; and (iii) gender equality only affects hidden hunger. We further provide evidence on the importance of spatial spillovers in GDP affecting the burden of hunger. Policy makers should therefore prioritize (i) enhancement of micronutrient density of cereals; (ii) diversification of production systems and consumer diets; and (iii) development of nutrition-sensitive food value chains.